INTERPERSONAL COMMUNICATION AND ORGANIZATIONAL ACTIVITIES IN INCREASING STUDENT ACADEMIC ACHIEVEMENT IN THE COVID-19 ERA - Raditya, Javier; Muhajirin, Bagus; Angriani, Maya Rezeki (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2023)
Smooth communication between lecturers and students will minimize the occurrence of miss communication so that the understanding of a material is not ambiguous and can be understood properly by students, this will certainly have a good impact on student academic achievement. However, during the pandemic, lectures were conducted online. Problems that arise as a result of lecture activities carried out online indirectly change the style of communication between lecturers and students, because in general and students' habits are easier to communicate and express every idea, problem and thought when face to face. This study aims to determine the effect of interpersonal communication and organizational activities on increasing student achievement simultaneously and partially. This research is a type of quantitative research with data analysis methods using multiple regression analysis with a sample of 87 students. The results showed that there was a partial influence between interpersonal communication variables on increasing student achievement and there was a partial effect between organizational activity variables on increasing student achievement. The results also show that there is a simultaneous influence between interpersonal communication variables and organizational activities.